The Use Of Supply Chain Management To Reduce Low Labour Productivity In Malaysian Public Sector Construction Projects - Loh, Yong Seng (2024)
Construction low labor productivity is a persistent issue in Malaysia, particularly evident in public sector construction projects, attributed to inefficient traditional practices prevalent in Malaysian construction industry for decades. To address this issue, contemporary practices like Supply Chain Management (SCM) have been advocated for their potential to enhance productivity through improved relationships, integration, flexibility, innovation, and improvement. However, a significant knowledge gap exists regarding the effective implementation of SCM in the Malaysian public sector construction context. There is limited research that specifically addressing the challenges and opportunities for SCM adoption in this sector. This research aims to fill this gap by investigating the causes of low labour productivity in Malaysian public sector projects and proposing a SCM framework to improve labour productivity. Employing a mixed-methods of quantitative and qualitative approaches, the study utilised questionnaire survey administered to 153 industry professionals involved in Tenth Malaysia Plan public sector construction projects, alongside with five sessions of semi-structured interviews. Statistical analysis, including ANOVA, Kruskal Wallis, T-Tests, and Mann-Whitney U, were conducted to identify primary contributors to labor productivity and validate factor groupings for the final research framework.